Growth dynamics and characteristics of fabricated Fiber Bragg Grating using phase mask method - Ho, Sze Phing; Ali, Jalil; Abdul Rahman, Rosly; Saktioto, Toto (Elsevier, 2009)
In this paper, Fiber Bragg Gratings (FBGs) are written by photoinduced refractive index changes in optical fibers. Experimental setup and results are presented to show the growth dynamics and the characteristics of the FBG that are written using phase mask method with different exposure time. In this paper, the effect of various UV exposure times and pulse energy during fabrication onto the reflectivity and Bragg wavelength has been defined.